Complications in resident-performed phacoemulsification cataract surgery at New Jersey Medical School. Issue 10 (12th April 2007) - Bhagat, Neelakshi; Nissirios, Nicholas; Potdevin, Lindsay; Chung, Jacob; Lama, Paul; Zarbin, Marco A; Fechtner, Robert; Guo, Suquin; Chu, David; Langer, Paul
Abstract : Aim: To describe the complications related to cataract surgery performed by phacoemulsification technique by third-year ophthalmology residents at New Jersey Medical School, who are trained to perform phacoemulsification without any prior experience with extracapsular extraction. Design: Retrospective, observational case series. Methods: A retrospective chart review of 755 patients who underwent cataract surgery by third-year residents between July 2000 and June 2005 at the Institute of Ophthalmology and Visual Science was performed. Details of intraoperative complications (posterior capsular rupture, vitreous loss, subluxation of lens fragments into the vitreous, extracapsular cases converted to phacoemulsification, retinal detachment, vitreous haemorrhage and haemorrhagic choroidals) of the cases done by phacoemulsification technique were recorded. Results were analysed and compared with complication rates reported from other residency programmes and from experienced ophthalmologists. Results: Of 755 cataract surgeries, 719 were performed using phacoemulsification technique. Posterior capsule disruption occurred in 48 (6.7%), vitreous loss in 39 (5.4%) and dislocated lenticular fragments in 7 (1.0%) of 719 cases that underwent phacoemulsification technique. Subsequent pars plana lensectomy was required in 5 (0.7%) cases; 1 case (0.1%) experienced retinal detachment and haemorrhagic choroidal detachment. Conclusion: The residents can perform phacoemulsification well with a very low complication rate, without prior training with extracapsular cataract extraction technique.